Aberrant expression of HMB45 and negative PRAME expression in halo nevi. (25th November 2020) - Ruby, Kristen N.; Li, Zhongze; Yan, Shaofeng
Abstract: Background: Traditionally, most cutaneous nevi show a gradient of HMB45 (human melanoma black 45) and negative PRAME (preferentially expressed antigen in melanoma) immunostaining, while melanomas often show irregularly positive, diffusely positive or completely negative HMB45 expression, and PRAME immunopositivity. However, we have occasionally observed benign halo nevi with loss of HMB45 gradient, raising diagnostic consideration for melanoma. The purpose of this study was to elucidate the expression pattern of HMB45 and PRAME in nevi with the halo phenomenon (NHP). Methods: PRAME and HMB45 staining patterns in 20 cases of NHP and 16 cases of conventional nevi were evaluated using light microscopy. An HMB45 gradient was defined as immunopositivity in only superficial melanocytes. HMB45 aberrant expression consisted of superficial and deep immunopositivity. Results: Aberrant HMB45 expression was observed in 10 of 20 NHP (50%). A gradient of HMB45 staining was seen in most conventional nevi, with only one showing focal weak expression in the deep dermis (6.3%). All cases of NHP and conventional nevi showed essentially negative immunostaining by PRAME. Conclusion: Aberrant HMB45 expression in NHP is not uncommon and may be a diagnostic pitfall. Negative PRAME immunostaining may be a reassuring finding to help differentiate halo nevus from malignant melanoma.